The index vein pointing to the origin of the migraine aura symptom: A case series. (16th June 2020) - Slavova, Nedelina; Denier, Niklaus; El-Koussy, Marwan; Wiest, Roland; Kellner-Weldon, Frauke; Fischer, Urs; Schankin, Christoph J.
Abstract : Objective: This case series describes and discusses the potential clinical utility of a prominent vein (index vein) found on susceptibility-weighted MRI during migraine aura that drains the cortical area responsible for patients' symptoms. Methods: Six patients with acute migraine aura had a prominent draining sulcal vein on emergency MRI done initially for suspected stroke. The location of the prominent vein was correlated to patients' symptoms, and the diameter was compared to the corresponding contralateral vein. Results: In our patients with typical migraine aura, an accentuated sulcal vein pointed towards the cortical area correlating with the clinical presentation. Such an index vein outstands the ipsilateral area of hypoperfusion and exceeds the corresponding contralateral vessel in diameter by a factor 2.0 ± 1.6 (mean ± SD). Conclusion: This case series provides a definition of an index vein in MRI pointing to the area where the patients' symptoms originate. Although confirmation in a larger systematic study is necessary, the presence of such an index vein might support that, in patients with an acute neurologic deficit, migraine aura is the underlying etiology.